أثر الطبيعة في شعر الغزل الأندلس ابن زيدون: أنموذجا - محمود، محمد عبدالرحمن (كلية الإمام الأعظم, 2021)
الحمد لله رب العالمين والصلاة والسلام على خاتم الأنبياء والمرسلين سيدنا محمد صلى الله عليه وسلم وعلى آله وصحبه أجمعين. أما بعد؛ عشق الإنسان الطبيعة وأعجب بها منذ القدم، ورأى فيها وفي جمالها مسرحا لأفكاره، وخياله، وصوره، وقد تأثر بها الشاعر والكاتب والأنسان العادي، وقد وجد الشعراء في الطبيعة ضالتهم في التعبير عن جمال المرأة وتغزلهم بها فقد ربطوا بين الطبيعة والمرأة، ومنهم الشاعر ابن زيدون، فشبه حبه لولادة كزهرة تنبت، أو شجرة تنمو، وكذلك وصف لنا جمال ولادة، بأجمل الأوصاف فوصفها بأنها زهرة جميلة جدا ذات عطر فواح، وهي صور موجودة لم ينفرد بها الشاعر بل لمسناها عند اغلب شعراء الأندلس، ويعود ذلك إلى الطبيعة الخلابة التي تفرض على أهل الأندلس هذه المشاعر والأحاسيس وهذا البحث جاء في بيان أهم هذه الصور التي جاء بها الشاعر ابن زيدون في الربط بين المرأة والطبيعة من خلال وصفه لمحبوبته ولادة بنت المستكفي بالله. Thank God, the Lord of the Worlds, prayers and peace on the ring of prophets and messengers Our Master Muhammad ( and on his gods and companions all but after: man loved nature and ad¬mired it since ancient times, and saw in it and in its beauty the scene of his ideas, imagination, and pictures, influenced by the poet, writer and ordinary man, poets in nature found their lost in express¬ing the beauty of women and flirting with them, they linked nature and women, including the poet Ibn Zaidon, likening his love to birth as a flower growing, or a tree growing, as well as describing to us the beauty of the birth, as well as describing the beauty of the birth of a tree, as well as a descrip¬tion of the beauty of the birth of a growing tree, as well as a description of the beauty of the birth of a growing tree. In the most beautiful descriptions, he described it as a very beautiful flower with a scent of flowers, which exists not unique to the poet but touched it among most andalusian poets, due to the picturesque nature that imposes on the people of Andalusia these feelings and feelings and this research came in the statement of the most important of these pictures that the poet Ibn Zaidon came in linking women and nature through his description of his beloved the birth of the daughter of the objector of God.
Keywords: الشعر الأندلس -- الشعر العربي -- الأدب العربي